Electrode catalyst layer and membrane electrode assembly

The integration of ionomer-adsorbing carbon fibers in the electrode catalyst layer addresses crack issues, enhancing mechanical strength and electrolysis performance in PEM water electrolysis devices.

JP7613498B2Active Publication Date: 2025-01-15TOPPAN HOLDINGS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023051806
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-01-15
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

Cracks in the electrode catalyst layer of membrane electrode assemblies in PEM type water electrolysis devices hinder proton and electron transfer, reducing water electrolysis performance.

Method used

Incorporating ionomer-adsorbing carbon fibers with a specific fiber diameter and hydrophilic treatment into the electrode catalyst layer to enhance mechanical strength and ionomer adsorption, forming conductive paths for protons or hydroxide ions.

Benefits of technology

The electrode catalyst layer achieves improved mechanical strength and water electrolysis performance with reduced crack occurrence, maintaining durability and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613498000001
    Figure 0007613498000001
  • Figure 0007613498000002
    Figure 0007613498000002
Patent Text Reader

Abstract

To provide an electrode catalyst layer and a membrane electrode assembly suitable for a water electrolysis apparatus which can suppress the occurrence of cracks in the electrode catalyst layer and improve the electrolytic performance of water.SOLUTION: An electrode catalyst layer 2 includes catalyst particles 12, an ionomer 13, and an ionomer adsorptive carbon fiber 14. The ionomer adsorptive carbon fiber 14 may have an adsorbed amount of ionomer of 10 mg or more per 1 g of the ionomer adsorptive carbon fiber, may have a diameter in the range of 50 nm or more and 1 μm or less, and may be a hydrophilic treated vapor grown carbon fiber (VGCF).SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode catalyst layer and a membrane electrode assembly suitable for a water electrolysis device. [Background technology]

[0002] In recent years, the movement to use hydrogen as a primary energy source, which is a CO2-free energy source that can be produced from various resources, has been accelerating in order to achieve carbon neutrality. As a method for producing such hydrogen, a method of electrolysis of water using renewable energy is considered promising. Generally, alkaline water electrolysis and polymer electrolyte membrane (PEM) water electrolysis are known as methods for electrolysis of water, and PEM water electrolysis in particular has attracted attention as a method that enables the miniaturization of water electrolysis equipment through highly efficient operation.

[0003] A PEM water electrolysis device generally includes a pair of main electrodes and a membrane electrode assembly provided between the pair of main electrodes. The membrane electrode assembly includes a laminate in which an anode-side electrode catalyst layer is provided on one surface of a proton-conductive solid polymer electrolyte membrane, and a cathode-side electrode catalyst layer provided so as to sandwich the solid polymer electrolyte membrane together with the anode-side electrode catalyst layer.

[0004] When external power is applied to the anode and cathode electrode catalyst layers, a water electrolysis reaction occurs on the catalyst in each electrode catalyst layer. At the anode, protons, electrons, and oxygen are produced from water, the protons move through the solid polymer electrolyte membrane, and the electrons move through an external circuit to the cathode, where hydrogen is produced.

[0005] The above-mentioned membrane electrode assembly is obtained by forming an electrode catalyst layer on one surface of a solid polymer electrolyte membrane, for example, by a coating method (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-83085 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the membrane electrode assembly described in Patent Document 1 may have cracks in the electrode catalyst layer, and there is room for improvement in terms of preventing the occurrence of cracks. The occurrence of cracks may inhibit the transfer of protons and electrons to the catalyst, thereby reducing the water electrolysis performance.

[0008] The present disclosure has been made in view of the above-mentioned problems, and has an object to provide an electrode catalyst layer and a membrane electrode assembly that can suppress the occurrence of cracks in an electrode catalyst layer and are suitable for a water electrolysis device with improved water electrolysis performance. [Means for solving the problem]

[0009] [1] An electrode catalyst layer comprising: catalyst particles; an ionomer; and an ionomer-adsorbing carbon fiber capable of adsorbing the ionomer.

[0010] [2] The electrode catalyst layer according to [1], characterized in that the ionomer-adsorbing carbon fiber has the ionomer adsorbed thereon, and the amount of the ionomer adsorbed is 10 mg or more per 1 g of the ionomer-adsorbing carbon fiber.

[0011] [3] The electrode catalyst layer according to [1] or [2], wherein the average fiber diameter of the ionomer-adsorbing carbon fibers is within the range of 50 nm or more and 1 μm or less.

[0012] [4] The electrode catalyst layer according to any one of [1] to [3], wherein the ionomer-adsorbing carbon fiber is a hydrophilically treated carbon fiber.

[0013] [5] The electrode catalyst layer according to any one of [1] to [4], wherein the ionomer-adsorbing carbon fiber is a vapor-grown carbon fiber (VGCF) that has been subjected to a hydrophilization treatment.

[0014] [6] The electrode catalyst layer according to any one of [1] to [5], which is for a water electrolysis device.

[0015] [7] The electrode catalyst layer according to any one of [6], which is a cathode-side electrode catalyst layer.

[0016] [8] A membrane electrode assembly comprising: a polymer electrolyte membrane; and an anode-side electrode catalyst layer and a cathode-side electrode catalyst layer sandwiching the polymer electrolyte membrane, wherein at least one of the cathode-side electrode catalyst layer and the anode-side electrode catalyst layer is the electrode catalyst layer according to any one of [1] to [7]. Effect of the Invention

[0017] According to the electrode catalyst layer and membrane electrode assembly of one embodiment of the present invention, a laminate for a water electrolysis cell having sufficient mechanical strength and improved water electrolysis performance can be provided using a simple method. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is an exploded perspective view illustrating a membrane electrode assembly having an electrode catalyst layer for a water electrolysis cell according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional schematic view of a cathode-side electrode catalyst layer according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Embodiment> Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. Here, the drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each layer, etc. differ from the actual ones. Furthermore, the embodiments shown below are merely examples of configurations for embodying the technical idea of ​​the present invention, and the technical idea of ​​the present invention is not limited to the materials, shapes, structures, etc. of the components described below. The technical idea of ​​the present invention can be modified in various ways within the technical scope defined by the claims.

[0020] [Membrane electrode assembly] As shown in FIG. 1, the membrane electrode assembly 11 of the present embodiment includes a polymer electrolyte membrane 1, an anode-side electrode catalyst layer 3 (shown on the lower side in FIG. 1) that sandwiches the polymer electrolyte membrane 1 from above and below, and a cathode-side electrode catalyst layer 2 (shown on the upper side in FIG. 1).

[0021] (Cathode side electrode catalyst layer 2) As shown in FIG. 2, the cathode side electrode catalyst layer 2 includes catalyst particles 12, an ionomer (polymer electrolyte) 13, and an ionomer-adsorbing carbon fiber .

[0022] (Cathode side catalyst particles) The catalyst particles 12 are particulate. When improvement of the activity of the catalyst particles is required, the average particle size of the catalyst particles is preferably 20 nm or less, and more preferably 5 nm or less. When stabilization of the activity of the catalyst particles is required, the average particle size of the catalyst particles is preferably 0.5 nm or more, and more preferably 1 nm or more.

[0023] The catalyst particles of the cathode electrode catalyst layer are catalysts for carrying out reduction reactions. The constituent materials of the catalyst particles can be platinum group elements, metals, alloys, oxides, double oxides, etc. of the metals. Examples of platinum group elements include platinum, palladium, ruthenium, iridium, rhodium, and osmium, and examples of metals include iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, and aluminum. The double oxide referred to here is an oxide made of two types of metals.

[0024] The catalyst particles of the cathode-side electrode catalyst layer may be supported on a carrier 15. The carrier is a particle that is conductive and is not eroded by the catalyst material. An example of the carrier is carbon particles. When an expansion of the electron conduction path is required, the particle size of the carrier is preferably 10 nm or more. When a reduction in the resistance value of the electrode catalyst layer is required, or an increase in the amount of catalyst particles supported is required, the particle size of the carrier is preferably 1000 nm or less, and more preferably 100 nm or less. An example of the material of the carrier is at least one selected from the group consisting of carbon black, graphite, activated carbon, and fullerene. The carbon black is at least one selected from the group consisting of acetylene black, furnace black, and ketjen black.

[0025] (Ionomer (polymer electrolyte)) The ionomer (polymer electrolyte) 13 is a polymer electrolyte having proton or hydroxide ion conductivity. The polymer electrolyte having proton conductivity has, for example, a particulate shape or a shape in which a plurality of particles are united. An example of the polymer electrolyte having proton conductivity is a fluorine-based polymer electrolyte or a hydrocarbon-based polymer electrolyte. An example of the fluorine-based polymer electrolyte is at least one selected from the group consisting of Nafion (registered trademark, manufactured by DuPont Co., Ltd.), Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.), Aciplex (registered trademark, manufactured by Asahi Kasei Co., Ltd.), and Gore-Select (registered trademark, manufactured by Gore Japan LLC). An example of the hydrocarbon-based cation exchange electrolyte is at least one selected from the group consisting of sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene. The polymer electrolyte having hydroxide ion conductivity is not particularly limited as long as it conducts hydroxide ions. For example, there are fluorine-based anion exchange electrolytes and hydrocarbon-based anion exchange electrolytes. Examples of fluorine-based electrolytes include perfluorocarbon-based electrolytes, and examples of hydrocarbon-based electrolytes include styrene-based electrolytes and acrylic-based electrolytes.

[0026] (Ionomer Adsorbent Carbon Fiber 14) The ionomer-adsorbing carbon fiber 14 can adsorb an ionomer. There is no particular limitation on the ionomer-adsorbing carbon fiber, but it may be a carbon fiber to which hydrophilicity has been imparted (hydrophilized carbon fiber), and for example, a hydrophilized carbon fiber manufactured to have hydrophilicity, or a hydrophilized carbon fiber that has been treated to impart hydrophilicity to a non-hydrophilic carbon fiber can be used. Examples of treatments that impart hydrophilicity to carbon fibers include ozone treatment, oxygen plasma treatment, electrolytic oxidation treatment, and mixed acid treatment.

[0027] The type of carbon fiber having ionomer adsorption is not particularly limited, and may be selected from carbon fibers such as carbon fibers, carbon nanofibers, carbon nanotubes, and carbon nanohorns. That is, the ionomer adsorbent carbon fiber may be solid or hollow. Among them, the carbon fiber is preferably vapor grown carbon fiber (VGCF).

[0028] The amount of ionomer adsorbed in the ionomer-adsorbing carbon fiber 14 is preferably 10 mg or more per 1 g of the ionomer-adsorbing carbon fiber.

[0029] In the ionomer-adsorbing carbon fiber 14, the ionomer (polymer electrolyte) is adsorbed on the surface of the carbon fiber, which improves the mechanical properties of the electrode catalyst layer and improves durability, such as by suppressing the occurrence of cracks in the electrode catalyst layer. In addition to the improvement in mechanical properties, the adsorption of the ionomer (polymer electrolyte) on the ionomer-adsorbing carbon fiber 14 forms a conductive path for protons or hydroxide ions, resulting in high electrolysis performance.

[0030] On the other hand, if the surface of the carbon fiber is not ionomer-adsorbent, it is difficult to adsorb the ionomer (polymer electrolyte). Therefore, it is presumed that the mechanical properties of the electrode catalyst layer are insufficient, it is difficult to suppress the occurrence of cracks, and durability cannot be improved. In addition, since the ionomer is dispersed, the formation of a conduction path for protons or hydroxide ions is inhibited, and electrolysis performance cannot be improved.

[0031] The average fiber diameter of the ionomer-adsorbing carbon fiber 14 is not particularly limited, but is preferably 50 nm to 1 μm, and more preferably 0.1 to 0.4 μm. In this case, the occurrence of cracks in the electrode catalyst layer is more likely to be suppressed. Also, the adhesion between the polymer electrolyte membrane and the electrode catalyst layer can be improved. Therefore, the occurrence of voids due to peeling between the polymer electrolyte membrane and the electrode catalyst layer can be suppressed, and the increase in resistance of the membrane electrode assembly caused by the voids can be more suppressed. When the average fiber diameter of the ionomer-adsorbing carbon fiber is less than 50 nm, it is estimated that the mechanical properties may be difficult to improve. Also, when the average fiber diameter of the ionomer-adsorbing carbon fiber is more than 1 μm, it is estimated that the ionomer-adsorbing carbon fiber may not be dispersed as an ink.

[0032] The average fiber diameter refers to the average diameter measured for the cross section of the exposed ionomer-adsorbed carbon fiber when the cross section of the electrode catalyst layer is observed using a scanning electron microscope (SEM). When the ionomer-adsorbed carbon fiber is cut obliquely to its long axis, an elliptical cross section is obtained. In this case, the diameter refers to the diameter of a perfect circle fitted along the short axis of the ellipse. When the cross section of the electrode catalyst layer is observed using a SEM, the surface of the ionomer-adsorbed carbon fiber may be exposed instead of the cross section of the ionomer-adsorbed carbon fiber. In this case, the diameter refers to the width of the fiber perpendicular to the long axis of the exposed ionomer-adsorbed carbon fiber. The average fiber diameter of the ionomer-adsorbed carbon fiber refers to the arithmetic average value of the fiber diameters obtained by similar measurements at at least 20 observation points.

[0033] As a method for exposing the cross section of the electrode catalyst layer, for example, a known method such as ion milling or ultramicrotome can be used.

[0034] The average fiber length of the ionomer-adsorbing carbon fiber is not particularly limited, but is preferably 500 nm or more, more preferably 1 μm or more. In this case, the ionomer-adsorbing carbon fiber is entangled to form pores of appropriate size in the electrode catalyst layer, and the mechanical properties of the electrode catalyst layer can be improved. However, the average fiber length of the ionomer-adsorbing carbon fiber is preferably 100 μm or less, more preferably 40 μm or less.

[0035] The average fiber length of the ionomer-adsorbing carbon fibers refers to the arithmetic mean value of the fiber lengths obtained by measuring at least 10 ionomer-adsorbing carbon fibers. The average fiber length of the ionomer-adsorbing carbon fibers in the electrode catalyst layer can be obtained by performing particle size distribution measurement using a solution in which the electrode catalyst layer is dissolved in a solvent. Specifically, the correlation between the average fiber length obtained by an electron microscope and the peak position in the particle size distribution measurement is grasped in advance, and the average fiber length of the ionomer-adsorbing carbon fibers in the electrode catalyst layer is obtained based on this correlation and the peak position obtained by the particle size distribution measurement.

[0036] The composition of the cathode side electrode catalyst layer 2 is not particularly limited, but the mass of the catalyst particles is taken as 1, the mass of the ionomer (polymer electrolyte) (solid content) can be 0.1 to 0.4, and the mass of the ionomer adsorbent carbon fiber can be 0.025 to 0.25.

[0037] (Anode side electrode catalyst layer 3) 2, the anode-side electrode catalyst layer 3 contains catalyst particles 22 and an ionomer (polymer electrolyte) 23. The anode-side electrode catalyst layer 3 contains ionomer-adsorbing carbon fibers 14, similar to the cathode-side electrode catalyst layer 2, thereby improving the mechanical properties of the electrode catalyst layer and improving durability. In addition to the improved mechanical properties, the polymer electrolyte is adsorbed onto the ionomer-adsorbing carbon fibers 14, forming a conduction path for protons or hydroxide ions, thereby achieving high electrolysis performance.

[0038] (catalyst particles) The catalyst particles 22 are particulate. When improvement of the activity of the catalyst particles is required, the average particle size of the catalyst particles is preferably 20 nm or less, and more preferably 5 nm or less. When stabilization of the activity of the catalyst particles is required, the average particle size of the catalyst particles is preferably 0.5 nm or more, and more preferably 1 nm or more.

[0039] The catalyst particles of the anode side electrode catalyst layer are catalysts for carrying out an oxidation reaction. The constituent materials of the catalyst particles can be metals included in the platinum group, metals other than the platinum group, or alloys, oxides, double oxides, and carbides thereof. Among them, ruthenium, rhodium, palladium, iridium, platinum, and alloys containing at least one of these metals are preferred because of their high catalytic activity. The catalyst particles may be one of the above examples, or a combination of two or more of them.

[0040] The catalyst particles of the anode-side electrode catalyst layer may be supported on a carrier 25. The carrier is a particle that is conductive and is not eroded in an oxidizing atmosphere. An example of the carrier is an oxide particle containing titanium, tin, or zirconium. When an expansion of the electron conduction path is required, the particle size of the carrier is preferably 10 nm or more. When a reduction in the resistance value of the electrode catalyst layer or an increase in the amount of catalyst particles supported is required, the particle size of the carrier is preferably 1000 nm or less, and more preferably 100 nm or less.

[0041] (Ionomer (polymer electrolyte)) The ionomer (polymer electrolyte) 23 on the anode side can be the same as the ionomer (polymer electrolyte) on the cathode side.

[0042] The composition of the anode side electrode catalyst layer 3 is not particularly limited, but the mass of the ionomer (polymer electrolyte) (solid content) can be 0.1 to 0.4, and the mass of the ionomer adsorbent carbon fiber can be 0.025 to 0.25, assuming that the mass of the catalyst particles is 1.

[0043] (Polymer electrolyte membrane 1) An example of the polymer electrolyte membrane 1 is a fluorine-based polymer electrolyte membrane or a hydrocarbon-based polymer electrolyte membrane having proton or hydroxide ion conductivity. The polymer electrolyte membrane is not particularly limited as long as it conducts protons or hydroxide ions.

[0044] An example of a fluorine-based polymer electrolyte membrane having proton conductivity is at least one selected from the group consisting of Nafion (registered trademark, manufactured by DuPont Co., Ltd.), Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.), Aciplex (registered trademark, manufactured by Asahi Kasei Co., Ltd.), and Gore-Select (registered trademark, manufactured by Gore Japan LLC). An example of a constituent material of a hydrocarbon-based polymer electrolyte membrane having proton conductivity is at least one selected from the group consisting of sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene.

[0045] An example of a fluorine-based anion exchange electrolyte membrane having hydroxide ion conductivity is a perfluorocarbon-based electrolyte membrane, while an example of a hydrocarbon-based anion exchange electrolyte membrane is a styrene-based electrolyte membrane or an acrylic-based electrolyte membrane.

[0046] In the case where it is required to improve the adhesion between the electrode catalyst layer and the polymer electrolyte membrane, if the constituent material of the polymer electrolyte of the electrode is a fluorine-based polymer electrolyte, it is preferable that the constituent material of the polymer electrolyte membrane is also a fluorine-based polymer electrolyte. Also, if the constituent material of the polymer electrolyte of the electrode is a hydrocarbon-based polymer electrolyte, it is preferable that the constituent material of the polymer electrolyte membrane is also a hydrocarbon-based polymer electrolyte. Furthermore, it is preferable that the constituent material of the polymer electrolyte membrane is the same as the constituent material of the polymer electrolyte of the electrode.

[0047] [Method for producing membrane electrode assembly] Next, an example of a method for producing the membrane electrode assembly having the above configuration will be described.

[0048] The membrane electrode assembly is produced by a method including the following first to third steps.

[0049] The first step is a step of producing ionomer-adsorbing carbon fibers by subjecting carbon fibers to an oxygen plasma treatment to impart hydrophilicity to the surfaces of the carbon fibers.

[0050] The second step is a step of producing a cathode-side catalyst ink containing catalyst particles, an ionomer (polymer electrolyte), the ionomer-adsorbing carbon fiber obtained in the first step, and a solvent, and a step of producing an anode-side catalyst ink containing catalyst particles, an ionomer (polymer electrolyte), and a solvent. In this step, the ionomer can be adsorbed onto the ionomer-adsorbing carbon fiber.

[0051] The third step is a step of applying the cathode-side catalyst ink and the anode-side catalyst ink obtained in the second step onto a polymer electrolyte membrane, and then drying the solvent, thereby forming a cathode-side electrode catalyst layer and an anode-side electrode catalyst layer on both sides of the polymer electrolyte membrane.

[0052] Detailed Description (1st step) In the first step, the surface of the carbon fiber is treated with oxygen plasma or the like to impart hydrophilicity to the surface of the carbon fiber, thereby producing an ionomer-adsorbing carbon fiber. The degree of hydrophilicity imparted to the surface of the carbon fiber, in other words, the degree of ionomer adsorption, can be adjusted by the time for which the carbon fiber is subjected to the hydrophilization treatment such as oxygen plasma treatment. The amount of ionomer adsorbed to the obtained ionomer-adsorbing carbon fiber can be calculated by contacting the carbon fiber with a dispersion liquid in which a predetermined concentration of ionomer is dispersed, filtering the dispersion with a predetermined filter (e.g., 0.3 to 0.5 μm in diameter), and measuring the concentration of the ionomer contained in the filtrate.

[0053] (2nd process) The cathode catalyst ink can be produced by mixing the catalyst particles, the ionomer (polymer electrolyte), the ionomer-adsorbing carbon fiber obtained in the first step, and a solvent. The anode catalyst ink can also be produced in the same manner. The solvent constituting the catalyst ink does not corrode the catalyst particles, the ionomer (polymer electrolyte), and the ionomer-adsorbing carbon fiber, and dissolves the ionomer (polymer electrolyte) or disperses it as a fine gel. An example of the solvent constituting the catalyst ink is at least one selected from the group consisting of alcohols, ketone-based solvents, ether-based solvents, and polar solvents. An example of the alcohols is at least one selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, and pentanol. An example of the ketone-based solvent is at least one selected from the group consisting of acetone, methyl ethyl ketone, pentanone, methyl isobutyl ketone, heptanone, cyclohexanone, methylcyclohexanone, acetonylacetone, and diisobutyl ketone. An example of the ether-based solvent is at least one selected from the group consisting of tetrahydrofuran, dioxane, diethylene glycol dimethyl ether, anisole, methoxytoluene, and dibutyl ether. An example of the polar solvent is at least one selected from the group consisting of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, diethylene glycol, diacetone alcohol, and 1-methoxy-2-propanol. The solvent constituting the catalyst ink may contain water, which has a high affinity with the polymer electrolyte.

[0054] When improved dispersibility of catalyst particles is required, the catalyst ink preferably contains a dispersant. Examples of dispersants include anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants. When improved dispersibility of the catalyst ink is required, a dispersion treatment is preferably performed in the production of the catalyst ink. Examples of dispersion treatments include stirring with a ball mill and a roll mill, stirring with a shear mill, stirring with a wet mill, stirring by applying ultrasonic waves, and stirring with a homogenizer.

[0055] When suppression of cracks on the surface of the electrode catalyst layer is required, the solid content of the catalyst ink is preferably 50% by mass or less.When an improvement in the film formation rate of the electrode catalyst layer is required, the solid content of the catalyst ink is preferably 1% by mass or more.

[0056] (3rd step) Examples of the method for applying the catalyst ink onto a substrate include the doctor blade method, the dipping method, the screen printing method, and the roll coating method. The substrate to which the catalyst ink is applied is a transfer sheet. Examples of the constituent material of the transfer sheet include fluororesin or organic polymer compounds other than fluororesin. Examples of fluororesin include ethylene tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroperfluoroalkylvinylether copolymer (PFA), and polytetrafluoroethylene (PTFE). Examples of organic polymer compounds include polyimide, polyethylene terephthalate, polyamide, polysulfone, polyethersulfone, polyphenylene sulfide, polyether ether ketone, polyetherimide, polyarylate, and polyethylene naphthalate.

[0057] In the above embodiment, the ionomer-adsorbing carbon fibers are provided in the electrode catalyst layer on the cathode side, but they may also be provided in the electrode catalyst layer on the anode side.

[0058] Hereinafter, the electrode catalyst layer and the membrane electrode assembly for a water electrolysis apparatus according to the present embodiment will be described with reference to specific examples and comparative examples, but the present embodiment is not limited to the following examples and comparative examples.

[0059] <Other effects> According to this embodiment, it is possible to manufacture a membrane electrode assembly for a water electrolysis system having an electrode catalyst layer with high mechanical properties and excellent electrolysis performance and durability, without using any complicated steps.

[0060] <Example 1> [Production of ionomer-adsorbing carbon fibers] Carbon fibers with an average fiber diameter of 150 nm (VGCF-H (registered trademark), vapor-grown carbon fibers manufactured by Showa Denko K.K.) were subjected to hydrophilization treatment by oxygen plasma treatment to obtain ionomer-adsorbing carbon fibers. Note that, when a fluorine-based polymer electrolyte (Nafion (registered trademark) dispersion) was used as the ionomer having proton conductivity, the ionomer-adsorbing carbon fibers of Example 1 were confirmed to have an ionomer adsorption amount of 10 mg or more per 1 g of the ionomer-adsorbing carbon fibers.

[0061] [Preparation of cathode-side catalyst ink] The catalyst particles, ionomer, and ionomer-adsorbing carbon fibers shown below were mixed in a solvent and dispersed for 30 minutes using a planetary ball mill to prepare a catalyst ink. A mixed solvent of ultrapure water and 1-propanol was used as the solvent for the catalyst ink. The volume ratio of ultrapure water to 1-propanol was 1:1. The catalyst ink was adjusted so that the solid content in the catalyst ink was 10% by mass. Catalyst particles: Pt-supported carbon particles Ionomer: Fluorine-based polymer electrolyte (Nafion® dispersion) Mixing ratio: For the catalyst ink, the mass of the catalyst particles was 1, the mass of the ionomer (solid content) was 0.4, and the mass of the ionomer-adsorbent carbon fiber was 0.05.

[0062] [Preparation of anode-side catalyst ink] The catalyst particles and ionomer shown below were mixed in a solvent and dispersed for 30 minutes using a planetary ball mill to prepare a catalyst ink. A mixed solvent of ultrapure water and 1-propanol was used as the solvent for the catalyst ink. The volume ratio of ultrapure water to 1-propanol was 1:1. The catalyst ink was adjusted so that the solid content in the catalyst ink was 10% by mass. Catalytic particles: Iridium oxide Ionomer: Fluorine-based polymer electrolyte (Nafion® dispersion) Mixing ratio: The catalyst ink had a catalyst particle mass of 1 and an ionomer (solids) mass of 0.2.

[0063] [Preparation of Membrane Electrode Assembly] The prepared cathode catalyst ink was applied to one side of a proton-conductive polymer electrolyte membrane (fluorine-based polymer electrolyte membrane) using a die coater to form a rectangular coating film measuring 50 mm long x 50 mm wide. The amount of the cathode catalyst ink applied was 0.5 mg / cm. 2 Then, a drying treatment was performed using an oven to volatilize the dispersion medium contained in the coating film, thereby forming a cathode-side electrode catalyst layer. Next, the prepared anode side catalyst ink was applied to the surface of the polymer electrolyte membrane opposite to the surface on which the cathode side electrode catalyst layer was formed, to form a rectangular coating film measuring 50 mm in length and 50 mm in width. The amount of the anode side catalyst ink applied was 0.5 mg / cm 2 Then, a drying treatment was carried out using an oven to volatilize the dispersion medium contained in the coating film, thereby forming an anode-side electrode catalyst layer, thereby obtaining a membrane electrode assembly. Both electrode catalyst layers in Example 1 were free of cracks and did not peel off from the polymer electrolyte membrane.

[0064] <Example 2> A membrane electrode assembly of Example 2 was obtained in the same manner as in Example 1, except that carbon fibers with an average fiber diameter of 0.8 μm were used as the carbon fibers in the ionomer-adsorbing carbon fibers. It was confirmed that when a fluorine-based polymer electrolyte (Nafion (registered trademark) dispersion) was used as the ionomer having proton conductivity, the ionomer-adsorbing carbon fibers of Example 2 had an ionomer adsorption amount of 10 mg or more per 1 g of the ionomer-adsorbing carbon fibers. Both electrode catalyst layers in Example 2 were free of cracks and did not peel off from the polymer electrolyte membrane.

[0065] <Example 3> [Production of ionomer-adsorbing carbon fibers] Carbon fibers with an average fiber diameter of 150 nm (VGCF-H (registered trademark), vapor-grown carbon fibers manufactured by Showa Denko K.K.) were subjected to a hydrophilization treatment by oxygen plasma treatment to obtain ionomer-adsorbing carbon fibers. It was confirmed that when a hydrocarbon-based anion exchange electrolyte was used as the ionomer having hydroxide ion conductivity, the ionomer-adsorbing carbon fibers of Example 3 had an ionomer adsorption amount of 10 mg or more per 1 g of the ionomer-adsorbing carbon fibers.

[0066] [Preparation of cathode-side catalyst ink] The catalyst particles, ionomer, and ionomer-adsorbing carbon fibers shown below were mixed in a solvent and dispersed for 30 minutes using a planetary ball mill to prepare a catalyst ink. A mixed solvent of ultrapure water and 1-propanol was used as the solvent for the catalyst ink. The volume ratio of ultrapure water to 1-propanol was 1:1. The catalyst ink was adjusted so that the solid content in the catalyst ink was 10% by mass. Catalyst particles: Pt-supported carbon particles Ionomers: Hydrocarbon-based anion exchange electrolytes Mixing ratio: The catalyst ink had a catalyst particle mass of 1, an ionomer (solid content) mass of 0.3, and an ionomer adsorbent carbon fiber mass of 0.05.

[0067] [Preparation of anode-side catalyst ink] The catalyst particles and ionomer shown below were mixed in a solvent and dispersed for 30 minutes using a planetary ball mill to prepare a catalyst ink. A mixed solvent of ultrapure water and 1-propanol was used as the solvent for the catalyst ink. The volume ratio of ultrapure water to 1-propanol was 1:1. The catalyst ink was adjusted so that the solid content in the catalyst ink was 10% by mass. Catalytic particles: Iridium oxide Ionomers: Hydrocarbon-based anion exchange electrolytes Mixing ratio: The catalyst ink had a catalyst particle mass of 1 and an ionomer (solids) mass of 0.3.

[0068] [Preparation of Membrane Electrode Assembly] The prepared cathode catalyst ink was applied to one side of a polymer electrolyte membrane (hydrocarbon-based anion exchange electrolyte membrane) with hydroxide ion conductivity using a die coater to form a rectangular coating film measuring 50 mm in length and 50 mm in width. The amount of the cathode catalyst ink applied was 0.5 mg / cm. 2 Then, a drying treatment was performed using an oven to volatilize the dispersion medium contained in the coating film, thereby forming a cathode-side electrode catalyst layer. Next, the prepared anode side catalyst ink was applied to the surface of the polymer electrolyte membrane opposite to the surface on which the cathode side electrode catalyst layer was formed, to form a rectangular coating film measuring 50 mm in length and 50 mm in width. The amount of the anode side catalyst ink applied was 0.5 mg / cm 2 Then, a drying treatment was carried out using an oven to volatilize the dispersion medium contained in the coating film, thereby forming an anode-side electrode catalyst layer, thereby obtaining a membrane electrode assembly. Both electrode catalyst layers in Example 3 were free of cracks and did not peel off from the polymer electrolyte membrane.

[0069] <Example 4> A membrane electrode assembly of Example 4 was obtained in the same manner as in Example 3, except that carbon fibers having an average fiber diameter of 0.8 μm were used as the carbon fibers in the ionomer-adsorbing carbon fibers. It was confirmed that when a hydrocarbon-based anion exchange electrolyte was used as the ionomer having hydroxide ion conductivity, the ionomer-adsorbing carbon fibers of Example 4 had an ionomer adsorption amount of 10 mg or more per 1 g of the ionomer-adsorbing carbon fibers. Both electrode catalyst layers in Example 4 were free of cracks and did not peel off from the polymer electrolyte membrane.

[0070] <Comparative Example 1> A membrane electrode assembly of Comparative Example 1 was obtained in the same manner as in Example 1, except that carbon fibers (VGCF-H (registered trademark), vapor-grown carbon fibers manufactured by Showa Denko KK) having an average fiber diameter of 150 nm were used without hydrophilization treatment instead of the ionomer-adsorbing carbon fibers. It was confirmed that when a fluorine-based polymer electrolyte (Nafion (registered trademark) dispersion) was used as the ionomer having proton conductivity, the carbon fibers of Comparative Example 1 had an ionomer adsorption amount of less than 10 mg per 1 g of carbon fibers.

[0071] In Comparative Example 1, when the cathode-side electrode catalyst layer was formed, there were no cracks and there was no peeling from the polymer electrolyte membrane. However, when the anode-side electrode catalyst layer was formed, cracks occurred in the cathode-side electrode catalyst layer and partial peeling from the polymer electrolyte membrane was observed.

[0072] <Comparative Example 2> A membrane electrode assembly of Comparative Example 2 was obtained in the same manner as in Example 2, except that carbon fibers with an average fiber diameter of 0.8 μm were used without hydrophilization treatment instead of the ionomer-adsorbing carbon fibers. It was confirmed that when a fluorine-based polymer electrolyte (Nafion (registered trademark) dispersion) was used as the ionomer having proton conductivity, the carbon fibers of Comparative Example 2 had an ionomer adsorption amount of less than 10 mg per 1 g of carbon fibers.

[0073] In Comparative Example 2, when the cathode-side electrode catalyst layer was formed, there were no cracks and there was no peeling from the polymer electrolyte membrane. However, when the anode-side electrode catalyst layer was formed, cracks occurred in the cathode-side electrode catalyst layer and partial peeling from the polymer electrolyte membrane was observed.

[0074] <Comparative Example 3> A membrane / electrode assembly of Comparative Example 3 was obtained in the same manner as in Example 1, except that the ionomer-adsorbing carbon fiber was not used. In Comparative Example 3, significant cracks were generated during the formation of the cathode-side electrode catalyst layer, and significant peeling from the polymer electrolyte membrane was observed, making it impossible to apply the anode-side catalyst ink.

[0075] <Comparative Example 4> A membrane / electrode assembly of Comparative Example 4 was obtained in the same manner as in Example 3, except that carbon fibers (VGCF-H (registered trademark), vapor-grown carbon fibers manufactured by Showa Denko KK) having an average fiber diameter of 150 nm were used without hydrophilization treatment instead of the ionomer-adsorbing carbon fibers. It was confirmed that when a hydrocarbon-based anion exchange electrolyte was used as the ionomer having hydroxide ion conductivity, the carbon fibers of Comparative Example 4 had an ionomer adsorption amount of less than 10 mg per 1 g of carbon fibers.

[0076] In Comparative Example 4, when the cathode-side electrode catalyst layer was formed, there were no cracks and there was no peeling from the polymer electrolyte membrane. However, when the anode-side electrode catalyst layer was formed, cracks occurred in the cathode-side electrode catalyst layer and partial peeling from the polymer electrolyte membrane was observed.

[0077] <Comparative Example 5> A membrane electrode assembly of Comparative Example 5 was obtained in the same manner as in Example 4, except that carbon fibers having an average fiber diameter of 0.8 μm were used without hydrophilization treatment instead of the ionomer-adsorbing carbon fibers. It was confirmed that when a hydrocarbon-based anion exchange electrolyte was used as the ionomer having hydroxide ion conductivity, the carbon fibers of Comparative Example 5 had an ionomer adsorption amount of less than 10 mg per 1 g of carbon fibers.

[0078] In Comparative Example 5, when the cathode-side electrode catalyst layer was formed, there were no cracks and there was no peeling from the polymer electrolyte membrane. However, when the anode-side electrode catalyst layer was formed, cracks occurred in the cathode-side electrode catalyst layer and partial peeling from the polymer electrolyte membrane was observed.

[0079] <Comparative Example 6> A membrane / electrode assembly of Comparative Example 6 was obtained in the same manner as in Example 3, except that the ionomer-adsorbing carbon fiber was not used. In Comparative Example 6, significant cracks were generated during the formation of the cathode-side electrode catalyst layer, and significant peeling from the polymer electrolyte membrane was observed, making it impossible to apply the anode-side catalyst ink.

[0080] When each of the membrane electrode assemblies obtained in Examples 1 to 4, Comparative Examples 1 to 2, and Comparative Examples 4 to 5 was immersed in water, the electrode catalyst layers of both Examples 1 to 2 did not peel off from the polymer electrolyte membrane, but the cathode-side electrode catalyst layers of Comparative Examples 1 to 2 and Comparative Examples 4 to 5 peeled off from the polymer electrolyte membrane. In addition, as a result of evaluating the water electrolysis performance using each membrane electrode assembly, the membrane electrode assemblies obtained in Examples 1 to 2 showed good electrolysis performance, but the membrane electrode assemblies obtained in Comparative Examples 1 to 2 and Comparative Examples 4 to 5 showed a significant decrease in electrolysis performance due to repeated electrolysis. From the results of the electrolysis performance of the membrane electrode assemblies prepared in the examples and the membrane electrode assemblies prepared in the comparative examples, it was confirmed that the adhesion strength between the cathode-side electrode catalyst layer and the electrolyte membrane was sufficient in the membrane electrode assemblies prepared in the examples, and good electrolysis performance was obtained.

[0081] Although the embodiment of the present invention has been described in detail above, in reality, the present invention is not limited to the above embodiment, and even if there are modifications within the scope of the gist of the present invention, they are included in the present invention. [Explanation of symbols]

[0082] 1...polymer electrolyte membrane, 2...cathode side electrode catalyst layer, 3...anode side electrode catalyst layer, 11...membrane electrode assembly.

Claims

1. A catalyst particle, an ionomer, and an ionomer-adsorbing carbon fiber capable of adsorbing the ionomer, The ionomer-adsorbing carbon fiber is a hydrophilically treated carbon fiber.

2. 2. The electrode catalyst layer according to claim 1, wherein the ionomer-adsorbing carbon fiber has the ionomer adsorbed thereon, and the amount of the ionomer adsorbed is 10 mg or more per 1 g of the ionomer-adsorbing carbon fiber.

3. 3. The electrode catalyst layer according to claim 1, wherein the average fiber diameter of the ionomer-adsorbing carbon fibers is within a range of 50 nm or more and 1 μm or less.

4. 3. The electrode catalyst layer according to claim 1 or 2, wherein the ionomer-adsorbing carbon fiber is a hydrophilically treated vapor grown carbon fiber (VGCF).

5. The electrode catalyst layer according to claim 1 or 2, which is a cathode-side electrode catalyst layer.

6. 3. A membrane electrode assembly comprising: a polymer electrolyte membrane; and an anode-side electrode catalyst layer and a cathode-side electrode catalyst layer sandwiching the polymer electrolyte membrane, wherein at least one of the cathode-side electrode catalyst layer and the anode-side electrode catalyst layer is the electrode catalyst layer according to claim 1.

Citation Information

Patent Citations

  • Paste for forming electrode catalyst layer, manufacturing method, film-electrode catalyst layer conjugant, gas diffusion electrode, solid polymer fuel cell, and manufacturing method of solid polymer water electrolysis cell

    JP2019083085A

  • A fuel cell's electrode and its a durability improvingmethod

    KR1020070112978A

  • Gas Diffusion Electrodes and Methods for Fabricating and Testing Same

    US20150376803A1

  • Membrane-electrode assembly for fuel cells and solid polymer fuel cell

    WO2020075777A1

  • Membrane electrode assembly and polymer electrolyte fuel cell

    WO2023068335A1